I See Sick People: Beliefs About Sensory Detection of Infectious Disease Are Largely Consistent Across Cultures - Fernandez-Tapia, A (Academic Press, 2025)
Identifying cues to contagious disease is critical for effectively tracking and defending against interpersonal infection threats. People hold lay beliefs about the types of sensory information most relevant for identifying whether others are sick with transmissible illnesses. Are these beliefs universal, or do they vary along cultural and ecological dimensions? Participants in 58 countries (N = 19,217) judged how effective, and how likely they were to use, cues involving each of the five major sensory modalities in an imagined social interaction during a flu outbreak. Belief patterns were strongly consistent across countries (sight > audition > touch > smell > taste), suggesting a largely universal conceptualization of the role of sensory information for interpersonal respiratory disease detection. Results also support a safe senses hypothesis, with perceivers reporting that they would use senses that function at a distance—and thus reduce pathogen transmission risk—more than would be expected given participants’ beliefs as to the efficacy of these senses for disease detection. Where societal variation did emerge, it was captured by a cohesive set of socio-ecological factors, including human development, latitude, pathogen prevalence, and population density. Together, these findings reveal a shared lens through which contagious respiratory disease is assessed, one that prioritizes minimizing risk to perceivers, and may offer leverage for designing interventions to improve public health. © 2025 Elsevier Inc.